Preparation of poly(methyl methacrylate)-zinc oxide hybrid nanoparticles via miniemulsion polymerization - Metanawin, Tanapak; Charoenchan, Maneerat; Metanawin, Siripan (Journal of Applied Research on Science and Technology (JARST), 2024)
The encapsulation of zinc oxide (ZnO) nanoparticles with poly(methyl methacrylate) in the presence of triethylene glycol dimethacrylate (TEGDMA) as a crosslinking agent was synthesized by the miniemulsion polymerization technique. The ZnO as a catalyze was varied from 1 wt% - 7 wt%. Several techniques were used to analyze the PMMA/TEGDMA/ZnO hybrid. The morphology and particle size distribution of the PMMA hybrid was observed using a field emission scanning electron microscope (FE-SEM). The diameter of the PMMA/TEGDMA/ZnO hybrid was in the range of 57 nm to 115 nm. The morphology of the PMMA/ZnO hybrids was sphere-shaped with a narrow particle size distribution and no agglomeration of the hybrids occurred. The encapsulation and crystalline structure of the PMMA ZnO hybrid were determined using a high-resolution transmission electron microscope (HR-TEM). The HR-TEM image demonstrated that the ZnO was encapsulated in the PMMA hybrid. In addition, the high magnification of the TEM image demonstrated the lattice spacing of ZnO and the diffraction mode image presented the crystalline structure of ZnO. Therefore, the photocatalytic properties of the PMMA/ZnO hybrid were examined via the degradation of methylene blue (MB) solution under dark and UV-A irradiation. It was found that the photocatalytic activities of the PMMA/ZnO hybrid increased when the ZnO content increased up to 7 wt%. The maximum MB degradation for PMMA/TEGDMA/ZnO 7 wt% and PMMA/ZnO 7 wt% were 80.1 % and 77.6 %, respectively. Thus, the photocatalytic efficiency of the PMMA/ZnO increased in the presence of TEGDMA as a crosslinking agent.